Assessment of the compatibility of Metarhizium anisopliae germination process with essential oils - Rosas-García, Ninfa M.; Alba-Moreno, Isela M.; Mireles-Martínez, Maribel; Villegas-Mendoza, Jesús M. (Acta Universitaria, 2019)
Metarhizium anisopliae (Hypocreales: Clavicipitaceae) is a fungus used in the control of insect pests, as well as various essential oils. These resources could be used in combination to control a pest if they are compatible. For this reason, the objective of this work was to determine the compatibility of the fungus M. anisopliae with various essential oils by evaluating the conidia germination process. Five strains of M. anisopliae and ten essential oils were used and compared in compatibility tests. The five fungal strains and the essential oils of garlic, cypress, eucalyptus, lemon, and orange were compatible. The essential oils of cinnamon, clove and geranium were incompatible, and the oils of lavender and peppermint had a variable compatibility depending on the concentration. The germination process of the conidia of the five strains was affected differently by the action of the essential oils tested.